(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: To find out the advantages and disadvantages of ultrasonic tonsillectomy by harmonic scalpel. Design and setting: A prospective study was conducted over a period of five years; from 01.07.2005 to 30.06.2010 in Comfort Nursing Home, 167B, Green Road, Dhaka, Bangladesh. Results: Hospital admitted 540 cases of ultrasonic harmonic scalpel tonsillectomy were included and analyzed. 360 cases were male; whereas 180 cases were female in this study. 0-10 years (168 cases) were the commonest age group of study people. Complications were rare, only two cases 0.37% of secondary hemorrhage had happened and no cases of reactionary hemorrhage was reported. Conclusion: The advantages are almost no bleeding, precise dissection of tonsils, less post operative pain, reduce postoperative discomfort, earlier return to normal activities, oral feeding immediately after operation and less operative time. Key words: Ultrasonic tonsillectomy; Harmonic scalpel. DOI: 10.3329/bjo.v16i2.6843 Bangladesh J Otorhinolaryngol 2010; 16(2): 91-95